Make Learning Fun and Get Out of the Way of the Smartphone Generation. - Willis, Scooter (Computer (00189162), 2018)
Students are ready to embrace the technology-driven 21st century. If we make learning fun and challenging—and then get out of the way—they will readily learn the skills needed to succeed in the future.